CULTURAL PRACTICES OF FEMALE CIRCUMCISION - Anis, Anisa; Perwiraningtyas, Pertiwi; Trishinta, Sirli Mardianna (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The cultural practice of female circumcision in Kalimantan, is not only based on local traditions and culture, but is also a must for the Muslim community. The circumcision is believed to be a worship that must be carried out, although religious guidance regarding female circumcision is still a matter of debate. The purpose of the study was to find out how the cultural practice of female circumcision.  This study used a descriptive qualitative design. The research was carried out in Kalimantan. The participants are parents, traditional healers, and health workers. The sampling technique was purposive with the inclusion criteria of living in the research area for at least 10 years and having seen firsthand the practice of circumcision against women. The collected data is then analyzed using the concepts proposed by Miles and Huberman. Most of the participants really respect the existence of female circumcision on the basis of religion or because of the words of parents who say that the girl must be circumcised. Most of the participants said they were not aware of the controversy about female circumcision, even heard that was prohibited. They believe that circumcision is mandatory and do not know that if it is done carelessly, it will be fatal. The cultural practice of female circumcision is still carried out from generation to generation because it is believed to be able to cleanse one's body from all dirt or najis.